Heme oxygenase-1 modulates ferroptosis by fine-tuning levels of intracellular iron and reactive oxygen species of macrophages in response to Bacillus Calmette-Guerin infection - Ma, Chenjie; Wu, Xiaoling; Zhang, Xu; Liu, Xiaoming; Deng, Guangcun (Frontiers in Cellular and Infection Microbiology, 2022)
Macrophages are the host cells and the frontline defense against of Mycobacterium tuberculosis (Mtb) infection, and the form of death of infected macrophages plays a pivotal role in the outcome of Mtb infections. Ferroptosis, a programmed necrotic cell death induced by overwhelming lipid peroxidation, was confirmed as one of mechanisms of Mtb spread following infection and the pathogenesis of tuberculosis (TB). However, the mechanism underlying the macrophage ferroptosis induced by Mtb infection has yet been fully understood. In the present study, transcriptome analysis revealed the upregulation of heme oxygenase-1 (HMOX1) and pro-ferroptosis cytokines, but downregulation of glutathione Peroxidase 4 (GPX4) and other key anti-lipid peroxidation factors in peripheral blood of both patients with extra-pulmonary tuberculosis (EPTB) and pulmonary tuberculosis (PTB). This finding was further corroborated in mice and RAW264.7 murine macrophage-like cells infected with Bacillus Calmette-Guerin (BCG). Mechanistic study further demonstrated that heme oxygenase-1 protein (HO-1) regulated the production of reactive oxygen species (ROS) and iron metabolism, and ferroptosis in BCG-infected murine macrophages. The knockdown of Hmox1 by siRNA resulted in a significant increase of intracellular ROS, Fe2+ and iron autophagy-mediated factor Ncoa4, along with the reduction of antioxidant factors Gpx4 and Fsp1 in macrophages infected with BCG. The siRNA-mediated knockdown of Hmox1 also reduced cell survival rate and increased the release of intracellular bacteria in BCG-infected macrophages. By contrast, scavenging ROS by N-Acetyl Cysteine led reduction of intracellular ROS, Fe2+ and Hmox1 concentrations, subsequentially inhibited ferroptosis, and the release of intracellular BCG in RAW264.7 cells infected with BCG. These findings suggest that HO-1 is an essential regulator of Mtb-induced ferroptosis, which regulates ROS production and iron accretion to alter macrophage death against Mtb infections.